Pendampingan Peningkatan Pemberdayaan Masyarakat Desa Kedanyang Kabupaten Gresik - Abi Hanif Dzulquarnain; Suaibatul Aslamiyah (Jurnal Pengabdian Manajemen, 2021)
The implementation of service activities is purely using a remote service model (online social media) which in this case uses Whatsapp Group media and Zoom meetings. This is because at the time of the implementation of the Gresik Regency service activity, the Covid-19 red zone was declared an emergency, so in order to support the reduction in the spread of the virus and the number of ODP in the Gresik Regency area, the service activity was decided to use social media online media. This service aims to provide a form of effort that can be made at the village community level in dealing with the COVID-19 pandemic at the economic level by utilizing electronic commerce media. The service partners are representatives of the Kedanyang village apparatus which in this case is represented by the village youth organization and the association of PKK women. service activities were decided to use online social media (Whatsapp), Whatsapp groups were used to facilitate communication between the management study program service team and representatives of the Kedanyang village apparatus, in this case represented by the village youth organization and the association of PKK women. Evaluation is to recap the responses, comments, and suggestions from the Kedanyang Village community who are members of the Whatsapp Group. The results of the online questionnaire that have been collected will be recapitulated, grouped, and economic analysis carried out in order to see the economic vulnerability of the community in Kedanyang Village. Furthermore, at the evaluation stage, they will also recap the results of the discussion in the Whatsapp Group. Based on the results of group discussions on Whatsapp and media zoom meetings, facts and information were obtained that the use of electronic commerce media as a form of increasing economic resilience in the Kedanyang Region is possible. However, it should be noted that the number of activities involving economic improvement on a micro scale such as handicrafts, food processing, beverage processing, and others is still very minimal in Kedanyang village.